2013
DOI: 10.1007/s11999-013-2851-8
|View full text |Cite
|
Sign up to set email alerts
|

Extensor Function After Medial Gastrocnemius Flap Reconstruction of the Proximal Tibia

Abstract: Background Reconstruction of the extensor mechanism after resection of the proximal tibia is challenging, and several methods are available. A medial gastrocnemius flap commonly is used, although it may be associated with an extensor lag. This problem also is encountered, although perhaps to a lesser extent, with other techniques for reconstruction of the extensor apparatus. It is not known how such lag develops with time and how it correlates with functional outcome. Questions/purposes We therefore (1) assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 31 publications
0
34
0
3
Order By: Relevance
“…The majority of osteoarticular allograft failures occurred within 24 months with infection being the most prevalent as had been reported previously [15,16]. It has been reported that the introduction of gastrocnemius flaps for soft tissue coverage after a proximal tibia resection has led to a decline in postoperative infection rates [13,20]. Three patients with limb salvage reconstruction failure could not be classified by Henderson classification: one patient (endoprosthetic group) with a postoperative lower limb ischemia that resulted in an above-knee amputation and two patients (osteoarticular allograft group) who developed severe osteoarthritis resulting in revision surgery to allograftcomposite prostheses.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The majority of osteoarticular allograft failures occurred within 24 months with infection being the most prevalent as had been reported previously [15,16]. It has been reported that the introduction of gastrocnemius flaps for soft tissue coverage after a proximal tibia resection has led to a decline in postoperative infection rates [13,20]. Three patients with limb salvage reconstruction failure could not be classified by Henderson classification: one patient (endoprosthetic group) with a postoperative lower limb ischemia that resulted in an above-knee amputation and two patients (osteoarticular allograft group) who developed severe osteoarthritis resulting in revision surgery to allograftcomposite prostheses.…”
Section: Discussionmentioning
confidence: 85%
“…Reconstruction of the extensor mechanism after proximal tibia tumor resection is a major concern and its success has shown some relationship with functional outcomes [2,3,5]. Reconstruction with allogeneic tissue from the proximal tibia allograft sutured to the recipient's remnant patellar tendon can restore and stabilize active knee extension, whereas the suture of the medial gastrocnemius flap to the extensor mechanism after endoprosthetic reconstruction has shown acceptable results [12][13][14]. We found that patients treated with allograft had better active extension with less extensor lag than attaching the patella ligament directly to the transposed gastrocnemius flap.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrocnemius and soleus muscles, being vascularized predominantly in their proximal regions, allow the rotation about the axis of the pedicle (good arc of rotation), without compromising vitality. They thus offer a good option for bone and soft tissue coverage of the Table 1 Table 1 Table 1 Table 1 Table 1 proximal and middle thirds of the leg, being the most used, usually individually [8][9][10][11][12][13][14][15][16] . In some situations, one may employ the soleus associated with one of the belies of the gastrocnemius 17 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…1). Weiterhin gilt grundsätzlich, dass die zuletzt verwendete Inzision oder die lateralste die geringste Nekroserate besitzt und deshalb zu bevorzugen ist [7]. Sicherlich spielen auch das Alter der Narbe mit entsprechend besserer Reperfusion und der Abstand zwischen den Inzisionen hinsichtlich des Nekroserisikos eine Rolle.…”
Section: Weichteile Und Zugangswahlunclassified